Experimental researches on gaze-based 3D interaction to stereo image display - Kwon, Yong-Moo; Shul, Jai Kyung (SPRINGER-VERLAG BERLIN, 2006)
There are several researches on 2D gaze tracking techniques for the 2D screen for the Human-Computer Interaction. However, the researches for the gaze-based interaction to the stereo images or contents are not reported. The 3D display techniques are emerging now for the reality service. Moreover, the 3D interaction techniques are much more needed in the 3D contents service environments. This paper addresses the gaze-based 3D interaction techniques. It is well known that there are characteristics of eye vergence according to the depth of object to be focused by human. This paper presents our experimental research results about the characteristics of eye vergence according to stereo image depth. Our research result is evaluated and applied to the gaze-based 3D interaction with the parallax barrier stereo image display system.